2008
DOI: 10.1111/j.1601-0825.2007.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of botulinum toxin type A injected into masseter muscle on a developing rat mandible

Abstract: The result demonstrated BTX-A influence on inhibitory action of the developing mandible because of apoptosis at the proliferation stage of the reserve zone of the condylar cartilage in developing rat mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 44 publications
2
21
0
1
Order By: Relevance
“…This finding coincides with that of our previous study (Kim et al, 2008), in which we concluded that weight differences may be the result of reduced muscle tonicity and mass induced by bilateral BTX-A injection.…”
Section: Overall Body Weights and Amounts Of Pellets Consumedsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding coincides with that of our previous study (Kim et al, 2008), in which we concluded that weight differences may be the result of reduced muscle tonicity and mass induced by bilateral BTX-A injection.…”
Section: Overall Body Weights and Amounts Of Pellets Consumedsupporting
confidence: 93%
“…The lack of statistical differences for these two measurements was presumably due to observational errors stemming from the difficulty in locating the condylar point and the tip of the coronoid process. Our finding of statistically smaller dimensions in Group 3 coincides with that of a previous study (Kim et al, 2008). In previous studies, histological findings revealed an inhibitory action of BTX-A due to induced apoptosis at the proliferation stage of the reserve zone of condylar cartilage in developing mandibles.…”
Section: Changes In Mandibular Measurementssupporting
confidence: 91%
See 2 more Smart Citations
“…Matic et al (2007) e Kim et al (2008) relatam que paralisia do músculo masseter resulta em atrofia do músculo e subsequentemente retardo do crescimento da mandíbula.…”
Section: Introductionunclassified